PENGARUH MODEL PEMBELAJARAN SAIN TEKNOLOGI MASYARAKAT (STM) TERHADAP KEMAMPUAN SOFT SKILL MAHASISWA - Yesi Budiarti; Siti Suprihatin (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2017)
Learning science of community technology is a learning model that links between science, technology and its benefits for the community environment. Science is the body of knowledge. The purpose of the implementation of learning model of community technology science is that learners have comprehensive knowledge about the link between technology science and its benefits for society. Thelearners are also required to be able to analyze and respond to the negative impacts caused by technology products related to the concept of science in certain subject matter topics. The ability of soft skill is very important given in the learning process. So that the graduates can be graduates who are ready to use in the world of work that not only has the ability of hard skills but also soft skills. Some soft skills, among others; communication, honesty, cooperation, interpersonal, work ethic, discipline, motivation, adapt, organize, confident, ethical, wise, creative, humorous, enterpreneurship.